Studying Synaptically Evoked Cortical Responses ex vivo With Combination of a Single Neuron Recording (Whole-Cell) and Population Voltage Imaging (Genetically Encoded Voltage Indicator) - Jang, Jinyoung; Zhu, Mei Hong; Jogdand, Aditi H.; Antic, Srdjan D. (Frontiers in Neuroscience, 2021)
In a typical electrophysiology experiment, synaptic stimulus is delivered in a cortical layer (1 – 6) and neuronal responses are recorded intracellularly in individual neurons. We recreated this standard electrophysiological paradigm in brain slices of mice expressing genetically encoded voltage indicators (GEVIs). This allowed us to monitor membrane voltages in the target pyramidal neurons (whole-cell), and population voltages in the surrounding neuropil (optical imaging), simultaneously. Pyramidal neurons have complex dendritic trees that span multiple cortical layers. GEVI imaging revealed areas of the brain slice that experienced the strongest depolarization on a specific synaptic stimulus (location and intensity), thus identifying cortical layers that contribute the most afferent activity to the recorded somatic voltage waveform. By combining whole-cell with GEVI imaging, we obtained a crude distribution of activated synaptic afferents in respect to the dendritic tree of a pyramidal cell. Synaptically-evoked voltage waves propagating through the cortical neuropil (dendrites and axons) were not static but rather they changed on a millisecond scale. Voltage imaging can identify areas of brain slices in which the neuropil was in a sustained depolarization (plateau), long after the stimulus onset. Upon a barrage of synaptic inputs, a cortical pyramidal neuron experiences: [a] weak temporal summation of EPSPs; and [b] afterhyperpolarization (intracellular recording), which are not represented in the GEVI population imaging signal (optical signal). To explain these findings ([a] and [b]), we used 4 voltage indicators (ArcLightD, chi-VSFP, Archon1 and di-4-ANEPPS) with different optical sensitivity, optical response speed, labeling strategy and a target neuron type. All 4 imaging methods were used in an identical experimental paradigm: Layer-1 synaptic stimulation, to allow direct comparisons. The population voltage signal showed paired-pulse facilitation, caused in part by additional recruitment of new neurons and dendrites. ‘Synaptic stimulation’ delivered in layer 1 depolarizes almost an entire cortical column to some degree.